Mapping the end times: American evangelical geopolitics and apocalyptic visions - Dittmer, Jason; Sturm, Tristan (Critical geopolitics, 2010)
Over the last quarter-century, evangelicalism has become an important social and political force in modern America. Here, new voices in the field are brought together with leading scholars such as William E. Connolly, Michael Barkun, Simon Dalby, and Paul Boyer to produce a timely examination of the spatial dimensions of the movement, offering useful and compelling insights on the intersection between politics and religion. This comprehensive study discusses evangelicalism in its different forms, from the moderates to the would-be theocrats who, in anticipation of the Rapture, seek to impose their interpretations of the Bible upon American foreign policy. The result is a unique appraisal of the movement and its geopolitical visions, and the wider impact of these on America and the world at large